A description of the larva and discussion of radiation in the phytotelm breeding damselfly genus Papuagrion in New Guinea (Odonata: Zygoptera: Coenagrionidae). Issue 3 (2nd July 2016) - Kalkman, Vincent J.; Orr, Albert G.
Abstract : The larva of Papuagrion is described and illustrated for the first time based on two specimens collected near Goroka, Papua New Guinea. The larvae were identified by matching the mitochondrial marker COI with that of an adult specimen collected at the same locality. The larvae were found in the leaf axils of Pandanus trees which agrees with earlier observations that adults are often encountered away from water, in the vicinity of Pandanus . Larvae collected from water pooled in the leaf bracts of several Pandanus trees in the Muller Range (PNG) are also thought to belong to the genus Papuagrion . Based on these records and further observations it is considered likely that all species of Papuagrion live in phytotelmata and that most or even all are found in Pandanus trees. Papuagrion is derived from a Papuan radiation of the genus Teinobasis, members of which inhabit standing or slow-flowing and often muddy waters, where the larvae probably develop, suggesting that the colonisation of phytotelmata offered by Pandanus trees has led to the radiation of Papuagrion, possibly because of the discrete and scattered nature of suitable habitats. The larvae show little difference morphologically from the few known Teinobasis larvae. The colonisation of phytotelmata as a larval habitat sometimes followed by an extensive radiation seems to have occurred independently several times within Coenagrionidae.